THE PROCESS OF REHABILITATION OF PERSONS RELEASED FROM PENAL INSTITUTIONS: PROBLEMS AND PROSPECTS (Web of Technology: Multidimensional Research Journal, 2024)
In this article, you can learn about the psychological condition of people who have been released from prison after a long term of imprisonment, as well as the prospects of their reintegration into society.